Kick double poling technique - biomechanical factors that discriminate between skill levels in cross-country skiers - Lindinger, S. J.; Göpfert, C.; Holmberg, H. C.; Müller, E. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Today's cross-country (XC) ski racing is determined by high speeds, reached by higher upper and lower body capacity and by further developed techniques. In contrast to double poling (DP), kick DP (DPK), is less focused and used, especially in sprint skiing. Due to more demanding tracks in classic skiing, the importance of DPK for race performance will grow, especially in high speed events. Compared to DP (Holmberg et al., 2005), DPK is much less investigated and there is little knowledge on speed control strategies in DPK (Nilsson, 2004). Thus the aim of the study was to identify cycle and force adaptations to different submaximal DPK speeds.